Relatório do estágio curricular supervisionado em Medicina Veterinária – área: reprodução de bovinos de corte - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This report describes the activities monitored and / or developed during the Supervised Curricular Internship in Veterinary Medicine ECSMV, carried out at the company Geneplan Reproduction Bovine. Acting in the area breeding beef cattle the company has its headquarters located in the municipality of Campo Grande, in the state of Mato Grosso do Sul. These activities took place under the supervision of the veterinarian Igor Mello Gentleman, applying the provision of management services and reproductive management of herds cattle. These include andrological examinations, protocols for the induction of puberty in heifers, estrous cycle synchronization and resynchronization, pregnancy diagnosis, health management, planning and advice on livestock. The activities were monitored / carried out in several rural properties in the Mato Grosso do Sul and Bolivia. The ECSMV occurred in the period of 7 January to 24 April 2019 with a total workload of 660 hours with emphasis on monitoring and carrying out artificial insemination protocols fixed time - IATF.
Report of the supervised internship in Veterinary Medicine - area: reproduction of beef cattle
Keywords: Medicina veterinária; Bovinocultura; Bovinocultura de corte; Reprodução animal; Bovinos; IATF; Veterinary medicine; Beef cattle; Animal reproduction; Cattle; CNPQ::CIENCIAS AGRARIAS